HYPOTHESIS OF GENDER SUBSCULTURES: GENDERLECT OF AMÉLIE NOTHOMB - Myronova , Natalia (PROBLEMS OF SEMANTICS, PRAGMATICS AND COGNITIVE LINGUISTICS, 2022)
At the present stage in national linguistics, gender research is developing quite intensively in several areas. Since this area of linguistics is currently under development, its study is considered promising. The use of a gender approach in social and humanitarian knowledge presents ample opportunities to reconsider culture, history, and linguistics, because its formation is, in fact, much more than just the emergence of a new theory. This is a fundamentally new theory, the adoption of which sometimes means a change in value orientations, a revision of many common ideas and truths. This is a kind of registers switching, change of accents, new projections, another plane of research. The article considers the hypothesis of gender subcultures and studies the concept of "genderlect". The basic, theoretical methodological approach made it possible to determine the range of existing problems with their conceptual vision. The sociological method allowed to correlate the studied gender parameters of A. Nothomb’s written language with the generally accepted characteristics of female and male language. The research of men’s and women’s language behavior is generalized, gender characteristics of male and female speech are given, features of written language of A. Nothomb are revealed and prospects of further scientific researches are outlined. The special contribution of the author to the development of the researched question is the generalization of theoretical achievements on the mentioned problem, the analysis of A. Nothomb’s written language, the identification of gender markers in the studied novels. It is established that the written language of the Belgian author does not correspond to the canons of today’s female language, and in many respects coincides with the generally accepted canons of the male style of writing. Thus, the existence of a special female language, which was assumed in early researches, is not confirmed. However, the works of recent years increasingly point to the fact that talking about genderlect is inappropriate and unscientific. The role of the subcultural factor in this case is greatly exaggerated. The differences between female and male language are not so significant, they are not manifested in every speech act and do not indicate gender being a determining factor in communication, as it was considered at the initial stage of feminist linguistics development. __________ References: • Zhukova, I. N. Slovar’ terminov mezhkul’turnoj kommunikacii [Glossary of Intercultural Communication Terms]. (Moskva, FLINTA : Nauka, 2012), 632. • Zhunusova, A. K. «Ponjatie genderlekt kak nabor priznakov muzhskoj i zhenskoj rechi [The concept of gender as a set of signs of male and female speech.]» Vestnik KASU 2 (2010): 135–139. • Goroshko, E. I. «Osobennosti muzhskih i zhenskih verbal’nyh associacij (opyt kachestvennoj interpretacii) [Features of male and female verbal associations (experience of high-quality interpretation)].» Materialy ІІ Mezhdunar. konf. [“Gender: jazyk, kul’tura, kommunikacija”], (Moskva, 2002): 77–86. • Krjuchkova, T. B. «Nekotorye jeksperimental’nye issledovanija osobennostej ispol’zovanija russkogo jazyka muzhchinoj i zhenshhinoj [Some experimental studies of the peculiarities of the use of the Russian language by men and women].» Problemy psiholingvistiki (Moskva, 1975): 186–200. • Lakoff, R. «Jazyk i mesto zhenshhiny [The language and place of a woman.]» Vvedenie v gendernye issledovanija. Chast’ II. Hrestomatija (Har’kov, HCGI, 2001; Sankt-Peterburg, Aleteja, 2001), 798. • Polishhuk, N. P. «Systemnyj harakter movlennja v komunikatyvnomu dyskursi [System nature of speech in communicative discourse.]» Problemy semantyky, pragmatyky ta kognityvnoi’ lingvistyky 37 (2020): 108–116. • Ujest, K., Zimmerman, D. «Sozdanie gendera [Gender creation.]» Hrestomatija feministskih tekstov (Sankt-Peterburg, Izd-vo "Dmitrij Bulanin", 2000): 193–220.